Indoor air quality in multifamily buildings - Telejko, Marek; Zender – Świercz, Ewa; Piotrowski, Jerzy (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The applicable legislation connected with the natural ventilation are ambiguous and sometimes contradictory. This leads to serious problems with natural ventilation. In most cases malfunction of the natural ventilation is due to the insufficient stream of air from the outside. The research showed that the microclimate is influenced not only by the incoming air stream, but also by the layout of the air supply.